Coffee and tea consumption and risk of prostate cancer in the European Prospective Investigation into Cancer and Nutrition. Issue 2 (16th November 2018) - Sen, Abhijit; Papadimitriou, Nikos; Lagiou, Pagona; Perez‐Cornago, Aurora; Travis, Ruth C.; Key, Timothy J.; Murphy, Neil; Gunter, Marc; Freisling, Heinz; Tzoulaki, Ioanna; Muller, David C.; Cross, Amanda J.; et al.
Abstract : The epidemiological evidence regarding the association of coffee and tea consumption with prostate cancer risk is inconclusive, and few cohort studies have assessed these associations by disease stage and grade. We examined the associations of coffee (total, caffeinated and decaffeinated) and tea intake with prostate cancer risk in the European Prospective Investigation into Cancer and Nutrition. Among 142, 196 men, 7, 036 incident prostate cancer cases were diagnosed over 14 years of follow‐up. Data on coffee and tea consumption were collected through validated country‐specific food questionnaires at baseline. We used Cox proportional hazards regression models to compute hazard ratios (HRs) and 95% confidence intervals (CI). Models were stratified by center and age, and adjusted for anthropometric, lifestyle and dietary factors. Median coffee and tea intake were 375 and 106 mL/day, respectively, but large variations existed by country. Comparing the highest (median of 855 mL/day) versus lowest (median of 103 mL/day) consumers of coffee and tea (450 vs . 12 mL/day) the HRs were 1.02 (95% CI, 0.94–1.09) and 0.98 (95% CI, 0.90–1.07) for risk of total prostate cancer and 0.97 (95% CI, 0.79–1.21) and 0.89 (95% CI, 0.70–1.13) for risk of fatal disease, respectively. No evidence of association was seen for consumption of total, caffeinated or decaffeinated coffee or tea and risk of total prostate cancer or cancer by stage, grade or fatality in this large cohort. Further investigations are needed to clarify whether an association exists by different preparations or by concentrations and constituents of these beverages. Abstract : What's new? Tea and coffee are popular all over the world, and many researchers have investigated how these beverages affect cancer risk. Results have been inconsistent. Here, the authors used data from the EPIC cohort to look for an association between consumption of coffee—total, caffeinated, and decaffeinated—and tea, and prostate cancer risk. Unlike many previous studies, which considered all prostate cancer, this study categorized the tumors based on stage, grade, and fatality. They found no association between coffee or tea consumption with total cancer risk, nor with fatal disease or cancer of any stage or grade.